A Qualitative Investigation on Risk Management Implementation in the Malaysian Public Sector - Ilias A.; Baidi N.; Ghani E.K.; Omonov A. (AESSRA, 2024)
This study aimed to examine the implementation of risk management in the public sector and, subsequently, identify the components of risk management that best fit the public sector. Interviews were conducted with 26 participants from nine government agencies to determine the Malaysian government's risk management and internal control processes. As a result, a new set of variables was identified for the public sector. These elements are the establishment of risk management in the government sector, the voluntary implementation of risk management, understanding risk management and internal control, the importance of risk management and internal control, the risk management process for the public sector, risk identification and investigation, understanding the risk management framework in the public sector, and the role of a consultant in risk management. This study contributed to the public sector by identifying potential aspects that may be crucial in ensuring the success of the early stages of risk management implementation. The outcomes of this study may benefit the public sector through an improved understanding of how to undertake risk management to ensure the success of risk management in Malaysia. 2023 Authors. All rights reserved.